Twenty-three arrests and around 10,000 cultural items seized - Europol Newsroom (Les Carnets de l’ACoSt)
On 18 November 2019, an international police operation involving over 350 police officers, supported by Europol (within the framework of EMPACT) and Eurojust, dismantled an international organized crime group involved in large-scale trafficking of looted archaeological items resulting in the arrest of 23 individuals, 80 house searches, and the seizure of around 10,000 cultural items, including hundreds of figurative terracottas.